Network vulnerability analysis based on the overall and inequity impacts of the distribution of the added travel time to the network users - Tahmasbi, Behnam; Haghshenas, Hossein; Birzhandi, Salehe (European Journal of Transport and Infrastructure Research, 2021)
Vulnerability has been a major concern in the performance evaluation of transportation networks. In the concept of vulnerability, the key step is to identify the critical link, which are the ones susceptible to severe operational degradation caused by any type of failure. Several studies have been devoted to this issue by introducing indicators that illustrate the network's operational degradation's overall impact. However, the impact of the interrupted network on users can be further evaluated using the inequity perspective. Here, we present a method to assess network vulnerability to operational degradation based on spatial inequity impacts. The importance of a link is determined by calculating the Gini-coefficient of the distribution of added travel time to the users when the link is disabled. Furthermore, the overall impact of link failure is calculated based on the total extra travel time. The final link's importance is determined by the non-dominated sorting method based on the Pareto optimality concept considering both overall and inequity objectives. Measures quantifying overall and inequity impacts of link failure allow planners to determine how this influences the disadvantaged distribution and help them make decisions associated with maintenance plans that consider link failure's equity impact.